THE PSYCHOLOGICAL TOLL OF GENDER INEQUALITY: UNDERSTANDING PERSONALITY TRAITS, STRESS COPING MECHANISMS, AND MENTAL HEALTH OUTCOMES (The Research of Medical Science Review, 2025)
Gender inequality continues to shape psychological well-being globally, particularly in low- and middle-income countries like Pakistan. This study investigates the psychological toll of gender inequality by exploring the predictive role of personality traits and stress coping mechanisms in mental health outcomes across genders. A total of 300 women aged 18 to 40 years, were recruited using a Purposive sampling technique. This study followed correlational, cross-sectional research design. The mean age for women was 28.9 years (SD = 6.1). Current study capturing a critical life stage characterized by social, familial, and economic responsibilities, where gender disparities are most impactful. Standardized, Urdu-adapted psychometric instruments were administered, including the Perceived Stress Scale (PSS; Cohen et al., 1983; Urdu version: Khalid et al., 2019), Coping Strategies Questionnaire (CSQ; Lazarus & Folkman, 1984; Urdu version: Kausar & Munir, 2004), Big Five Inventory (BFI; John & Srivastava, 1999; Urdu version: Riaz et al., 2010), and the Depression, Anxiety, and Stress Scale (DASS-21; Lovibond & Lovibond, 1995; Urdu version: Aslam, 2007). Data were analyzed using descriptive statistics, Pearson correlations, multiple regression, and Structural Equation Modeling (SEM) to test mediation and moderation. Women reported significantly higher perceived stress, neuroticism, and maladaptive coping than men. Neuroticism predicted maladaptive coping, which mediated its relationship with psychological distress. Conscientiousness and extraversion were associated with adaptive coping and lower mental health symptoms. Moderation analysis revealed that perceived stress amplified the impact of neuroticism on maladaptive coping among women. These findings highlight the need for culturally contextualized, gender-sensitive psychological interventions in addressing the mental health burden of inequality.